(untitled) (Global Journal of Medical Research, 2024)
Objective To evaluate the association between chemotherapy and radiotherapy with occurrence of oral complications in cancer patients Methods This cross-sectional study included 399 adults in cancer treatment in a High Complexity Oncology Care Unit HCOCU in Minas Gerais Brazil Participants adults 18 years were included in the study who undergoing treatment or are being monitored after treatment at the Oncological Center of the Casa de Caridade Nossa Senhora do Perp tuo Socorro between 2017 and 2019 Outcomes were assessed through a questionnarie about selfreported oral complications such as xerostomia halitosis taste changes dietary modifications trismus mucositis and the presence of infection inflammation